Bite force is limited by the force–length relationship of skeletal muscle in black carp, Mylopharyngodon piceus - Gidmark, Nicholas J. (The Royal Society, 2013)
Bite force is critical to feeding success, especially in animals that crush strong, brittle foods. Maximum bite force is typically measured as one value per individual, but the force–length relationship of skeletal muscle suggests that each individual should possess a range of gape height-specific, and, therefore, prey size-specific, bite forces. We characterized the influence of prey size on pharyngeal jaw bite force in the snail-eating black carp (Mylopharyngodon piceus, family Cyprinidae), using feeding trials on artificial prey that varied independently in size and strength. We then measured jaw-closing muscle lengths in vivo for each prey size, and then determined the force–length relationship of the same muscle in situ using tetanic stimulations. Maximum bite force was surprisingly high: the largest individual produced nearly 700 N at optimal muscle length. Bite force decreased on large and small prey, which elicited long and short muscle lengths, respectively, demonstrating that the force–length relationship of skeletal muscle results in prey size-specific bite force.